2013
DOI: 10.3233/jad-122101
|View full text |Cite
|
Sign up to set email alerts
|

Early Reproductive Experiences in Females Make Differences in Cognitive Function Later in Life

Abstract: Women experience dramatic changes in hormones, mood and cognition through different periods of their reproductive lives, particularly during pregnancy and giving birth. While limited human studies of early pregnancy and motherhood showed alteration of cognitive function in later life, research conducted on rodents showed a persistent improvement of learning and memory performance in females with history of giving birth (primiparous or multiparous) compared to virgin controls (nulliparous). In this mini review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…For example, recent animal studies showed that endogenous sex hormone levels changed by reproductive experience in females are associated with enhanced hippocampus-dependent memory [95], supporting the theory that parity may result in a higher level of exposure to estrogens, and as a consequence, changes the way the brain responds to estrogens in later life [50; 96]. …”
Section: Sex Differences In Cognitionmentioning
confidence: 95%
“…For example, recent animal studies showed that endogenous sex hormone levels changed by reproductive experience in females are associated with enhanced hippocampus-dependent memory [95], supporting the theory that parity may result in a higher level of exposure to estrogens, and as a consequence, changes the way the brain responds to estrogens in later life [50; 96]. …”
Section: Sex Differences In Cognitionmentioning
confidence: 95%
“…For example, the emerging data indicate that the normal reproductive experience or motherhood can mitigate AAMI (Gatewood et al 2005) and alter the cellular response to estrogens in older hippocampi in rats (Barha and Galea 2011). These results suggest that the normal reproduction experience has a long-lasting and extensive influence on the AAMI in female rodents (Li et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…These data imply a long-term, significant impact of adverse pregnancy on behaviors in mothers. Given normal reproduction experience and the adverse gestational conditions mentioned above can chronically affect cognitive functioning or other behaviors (Li et al 2013;Mielke et al 2016;Darnaudéry et al 2004), so it is plausible to hypothesize that gestational inflammation can impact the AAMI and corresponding neural substrates in the mother-self during aging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies showed that endogenous estrogen levels changed by reproductive experience in females are associated with enhanced hippocampus-dependent memory [107; 108]. Furthermore, sex steroids have been linked to many of the mechanisms thought to be associated with cognitive decline and several types of dementia.…”
Section: Introductionmentioning
confidence: 99%